Raw CTD data and microstructure measurements for revisiting Thorpe scale analysis of diapycnal mixing in the Southern Ocean - Park, Young-hyang; Durand, Isabelle; Lee, Jae-hak; Provost, Christine (SEANOE, 2022)
The data set presented here is related to an article on revisiting Thorpe scale analysis in the Southern Ocean (submitted to GRL). The data enables the validation of a revised Thorpe scale analysis at 8 stations in the Southern Ocean: 1) 7 TurboMAP/CTD stations in Drake Passage in April 2009; 2) 1 TurboMAP/CTD station in the Kerguelen region in October 2011 Reference to be cited as: Young-Hyang Park, Isabelle Durand, Jae-Hak Lee, Christine Provost. Revisiting Thorpe scale analysis for accessing a relable diapycnal diffusivity in the Southern Ocean. Submitted to GRL